Oxygen therapy assessment in adult patients at an intensive care unit of a teaching hospital - Maria Lucileia BARROS; Bianca Leite SANTOS; Geovanna Cunha CARDOSO; Francisco José LIMA; Daniela Teles OLIVEIRA; Géssica Uruga OLIVEIRA; Eliene Lima ALMEIDA; Ana Paula VASCONCELOS; Fábio Ramalho AMORIM (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2023)
Objective: to carry out a situational diagnosis of the adequacy of oxygen therapy prescriptions in an adult intensive care unit (ICU) of a teaching hospital in Northeast Brazil. Methods: this is a cross-sectional, descriptive, retrospective, and quantitative study, in which the medical records and prescriptions of patients using oxygen, admitted to the ICU between March and June 2021, were evaluated, based on the guidelines of the British Thoracic Society (BTS). This advocates that target O₂ saturation, delivery device and initial O₂ flow are minimum and mandatory criteria for prescribing oxygen therapy. The project is part of a larger research approved by the ethics committee in research involving human beings with the number 3,709,534 (CAAE n° 22984119.9.0000.5546). Results: The sample consisted of 42 patients. Of these, 90.5% had an indication for the use of oxygen, but only 71.4% had oxygen therapy in the prescription. No prescription contained the target saturation, 64.3% had the delivery device, and 16.7% contained the initial flow or inspired fraction of O₂. Conclusion: The study demonstrated that oxygen prescriptions in the researched care unit do not meet the BTS recommendations and that interventions should be performed to make care safer.